2017
DOI: 10.1002/2016ja023337
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive scattering of electrons by electron holes around injection fronts

Abstract: Van Allen Probes have detected nonlinear electrostatic spikes around injection fronts in the outer radiation belt. These spikes include electron holes (EH), double layers, and more complicated solitary waves. We show that EHs can efficiently scatter electrons due to their substantial transverse electric fields. Although the electron scattering driven by EHs is diffusive, it cannot be evaluated via the standard quasi‐linear theory. We derive analytical formulas describing local electron scattering by a single E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(96 citation statements)
references
References 103 publications
(138 reference statements)
3
90
1
Order By: Relevance
“…The properties of phase space holes observed by the Burst 1 data are now compared with phase space hole properties derived from Burst 2 observations, specifically with Vasko, Agapitov, Mozer, Artemyev, Drake, and Kuzichev (), where the amplitude, phase velocity, magnetic spike signature, parallel width, and potential depth of 100 electron phase space holes were examined using Burst 2 data. Vasko, Agapitov, Mozer, Artemyev, Krasnoselskikh, and Bonnell () used the Vasko, Agapitov, Mozer, Artemyev, Drake, and Kuzichev () results to define typical electron hole properties from which they derived diffusion coefficients describing the diffusive scattering of electrons by electron phase space holes. The diffusion coefficients computed by Vasko, Agapitov, Mozer, Artemyev, Krasnoselskikh, and Bonnell () were based on electron hole parameters as determined using amplitude‐biased Burst 2 data.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of phase space holes observed by the Burst 1 data are now compared with phase space hole properties derived from Burst 2 observations, specifically with Vasko, Agapitov, Mozer, Artemyev, Drake, and Kuzichev (), where the amplitude, phase velocity, magnetic spike signature, parallel width, and potential depth of 100 electron phase space holes were examined using Burst 2 data. Vasko, Agapitov, Mozer, Artemyev, Krasnoselskikh, and Bonnell () used the Vasko, Agapitov, Mozer, Artemyev, Drake, and Kuzichev () results to define typical electron hole properties from which they derived diffusion coefficients describing the diffusive scattering of electrons by electron phase space holes. The diffusion coefficients computed by Vasko, Agapitov, Mozer, Artemyev, Krasnoselskikh, and Bonnell () were based on electron hole parameters as determined using amplitude‐biased Burst 2 data.…”
Section: Observationsmentioning
confidence: 99%
“…Using the Van Allen Probes high‐resolution electric and magnetic field time series data (burst data), researchers have demonstrated that this broadband power is due to waves and structures such as electron‐acoustic solitons (Agapitov et al, ; Mozer et al, ; Vasko, Agapitov, Mozer, Bonnell, et al, ), ion‐acoustic double layers (Malaspina et al, ), electron phase space holes (Malaspina et al, ; Vasko, Agapitov, Mozer, Artemyev et al, ; Vasko, Agapitov, Mozer, Artemyev, Krasnoselskikh, & Bonnell, ), nonlinear whistler mode waves (Gao et al, ; Mozer et al, ), and kinetic Alfvén waves (Chaston et al, , ; Malaspina, Claudepierre, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They play an important role in plasma dynamics (e.g., Hutchinson, 2017, and references therein); in particular, they provide a mechanism for scattering and heating of electrons (Vasko et al, 2017) and can increase the rate of magnetic reconnection (Drake et al, 2003). They play an important role in plasma dynamics (e.g., Hutchinson, 2017, and references therein); in particular, they provide a mechanism for scattering and heating of electrons (Vasko et al, 2017) and can increase the rate of magnetic reconnection (Drake et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Theory [ Artemyev et al ., ; Vasko et al ., ; Vasko et al ., , ], earlier observations [ Mozer et al ., , , ], and the observations in this paper all show that TDSs accelerate and pitch angles scatter keV equatorial electrons to lower altitude mirror points where they either produce auroras or are further processed by lower altitude TDS to create auroras on field lines having the TDS. The typical speed of a TDS is ~5000 km/s, which is the speed of a 70 eV electron.…”
Section: Discussion—electron Scattering By Time Domain Structuresmentioning
confidence: 87%